Kajian Preferensi Konsumen Terhadap Buah-Buahan Lokal di Kota Banjarbaru - Muzdalifah Muzdalifah (Universitas Lambung Mangkurat, 2012)
The Study is purposed to know the consumer preference on local fruits and to analyze the competitiveness of local and imported fruits in Banjarbaru Municipality. Descriptive analysis was applied in order to describe systematically the facts and the nature of the population. Samples were selected by survey method, where 40 respondents were taken accidentally. Then, multi-attribute Fishbean model was applied to know the factors which affect consumer preference. The results show, the consumer believes that price, taste, color, freshness, aroma, size and high vitamin level, are factors considered to choose and consume local fruits. The order of importance of the local fruits attributes rated by consumers is: sweet taste, freshness, vitamin content, bigger in size, lower price, attracted aroma and color. Generally, imported fruits have advantage in terms of taste, color, aroma, size and vitamin. In another vein, the local fruits have advantage in the term of price and freshness.